Analysis of the Model for the Application of Religious Moderation Values in Senior High School: A Study on MAN 1 Boyoloali - Muhammad Lutfi Hamid; Muhammad Nanang Qosim (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
This study aims to analyze the application of religious moderation values through various learning models in MAN 1 Boyolali, such as seminars, discussions, and workshops. The research uses a qualitative descriptive approach with data obtained through activity documentation. The study results show that the model of applying the value of religious moderation, such as seminars and discussions, can increase students' understanding of tolerance, deliberation, and respect for diversity. However, implementing the model still faces obstacles, such as uneven student participation and lack of resources. Overall, the application of religious moderation values positively impacts the formation of moderate student character, although it requires continuous mentoring and evaluation to increase its effectiveness. This study underscores the importance of collaboration between teachers, students, and the community in creating an educational environment that supports the values of moderation.